Narcotic pills in the Palestinian governorates: An academic study of the most prevalent types, factors influencing their spread, their health, economic, social, and security effects, and mechanisms for confronting them (Al-Farooq Journal of Sciences, 2026)
This study aims to identify the most common narcotic pills that have been seized by the Palestinian security services and documented in official reports. The study's problem is summarized in the main question: "What are the most common narcotic pills that have been seized in the Palestinian governorates by the security services?" The importance of the study lies in its shedding light on the concept of narcotic pills, their types that are prevalent in the governorates, the reasons for their spread, the effects resulting from their spread in terms of health, economic, social and security aspects, and the mechanisms for confronting their spread. The study is divided into two sections:Section One: Narcotic Pills – Concept, Types, and Reasons for SpreadSection Two: Health, Economic, Social, and Security Effects Resulting from the Spread of Narcotic Pills and Mechanisms for Addressing ThemThe study concluded with a set of results and recommendations, and perhaps its most important results are the following: - There is a spread of the phenomenon of drug pill abuse in the northern and southern Palestinian governorates, and evidence of this is the high rate of seizures by security forces. Drug pills are a new type of modern drug that contains substances with different medical effects, which may be narcotic, hallucinogenic, analgesic, hypnotic, sedative, or psychoactive. The spread of drug pills in the governorates is due to a set of health, social, economic, and security factors. There are a set of mechanisms that must be adopted to reduce the spread of the phenomenon of drug pill abuse and trade in Palestinian society.Among the most important recommendations are: the necessity of adopting comprehensive and integrated national preventive mechanisms to reduce the phenomenon of narcotic pill abuse; and the necessity of strengthening cooperation among health, security, judicial, social, media, and academic institutions in preventing and combating narcotic pill abuse.
Keywords: narcotic pills, psychoactive substances, Palestinian governorates, countermeasures